A Numerical Model to Study the Response of Piles under Lateral Loading in Unsaturated Soils - Leonardo Maria Lalicata; Giada Maria Rotisciani; Augusto Desideri; Francesca Casini (Geosciences, 2021)
The interaction between a laterally loaded pile and the surrounding soil is typically limited to the shallower soil layer. Often, this zone is above the water table and therefore the interaction takes place under unsaturated conditions. The available evidence is scarce but suggests that unsaturated conditions play a major role on the pile’s response. The actual mechanisms governing the soil–pile interaction under unsaturated soil conditions are not understood entirely, and this paper provides a useful insight on this topic. The analysis is carried out with a fully coupled three-dimensional numerical model, the soil behaviour is simulated with a Modified Cam Clay Model extended to unsaturated conditions. The model accounts for the increase in stiffness and strength of unsaturated soils as well as the volumetric collapse upon wetting. The constitutive model is calibrated on the laboratory data and validated against centrifuge data with satisfying agreement. The results highlight the substantial differences in the soil reaction against the pile depending on different water saturation profiles. The study also shows that the influence of unsaturated conditions on the pile response increases as the pile’s flexibility increases. Comparing the findings with currently available design methods such as the p-y curves, it is found that these do not adequately describe the unsaturated soil reaction against the pile, which opens the door for new research in the field. The proposed numerical model is a promising tool to further investigate the mechanisms underlying the soil–pile interaction under unsaturated soils.